4CPS-385 Impact of fully automatised central intravenous additive service (CIVAS) on daily nursing practice. (14th March 2021) - Mura, F; Leoni, S; Vagnoni, F; Federici, M; Marinozzi, A; Guglielmi, S; Capone, C; Felicetti, S; Badaloni, M; Pompilio, A
Abstract : Background and importance: The introduction of the pharmacy based central intravenous additive service (CIVAS) enabled the batches production of ready-to-administer, non-hazardous intravenous drugs by using the robotic system APOTECAunit. The clinical benefits in terms of a higher quality aseptic process, reduced medication errors and increased quality control testing have been demonstrated. Aim and objectives: The aim of the study was to evaluate the impact of the fully automatised CIVAS on the working efficiency of the wards by measuring the time saved in daily nursing practice. Material and methods: The study was conducted over 3 months with data collected before and after introducing the CIVAS. Overall, three wards were analysed: inpatient haematology (IH), cardiac surgical (CS) and infectious diseases (ID). The nursing staff was observed daily for 4 weeks. Different tasks associated with the following intravenous drugs supplied by the CIVAS were recorded: ondansetron, palonosetron, cefazoline, piperacillin–tazobactam, ceftriaxone and dexamethasone. The average working time spent on managing intravenous drugs was calculated per full time equivalent (FTE), including direct activities (intravenous drug preparation) and indirect activities (procurement of drugs and medical devices, drugs inventory management, drug ordering). 1.0 FTE was equivalent to a nurse working 8.0 hours per day, 5 days per week. Results: The overall time spent on managing intravenous drugs decreased from 1.6 to 0.7 hours/day/FTE in the IH ward, from 0.75 to 0.15 hours/day/FTE in the CS ward and from 2.1 to 0.43 hours/day/FTE in the ID ward. Before implementing the CIVAS, on average 1.0 FTE spent 0.5 hours/day on preparing intravenous drugs, whereas the intravenous drug preparation time was reduced to zero afterwards in each of the three wards. The time spent on procurement decreased by 80% in the IH ward, by 60% in the CS ward and by 75% in the ID ward. The nursing staff shortened the time required for drug inventory management by 33% in the CS ward and by 50% in the IH and ID wards. In all wards, ordering of drugs was reduced by at least 50%. Conclusion and relevance: The study showed that the centralised, automated preparation of intravenous drugs optimised the working efficiency of the wards, thereby allowing the nursing staff to dedicate more time to perform tasks directly involved with patient care. References and/or acknowledgements: Conflict of interest: No conflict of interest